2017
DOI: 10.18805/ijar.b-745
|View full text |Cite
|
Sign up to set email alerts
|

Cattle husbandry practices management adopted by dairy farmers in Eastern semi-arid region of Algeria: A study of Setif Area

Abstract: This study was conducted in Eastern semi-arid region of Sétif (Algeria). 63 dairy cattle farmers were surveyed through personal interview using a well-structured questionnaire to collect the information about cattle husbandry practices followed in the study area. The data were analysed using descriptive statistics performed with SPSS software (version 19). The results revealed that the majority of farmers (68.85%) rely on family labor and 31.15 per cent use wage labor. As for the age group, operators aged betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
1
1
Order By: Relevance
“…The average age of farmers is 35 years. Benidir et al (2017) reported the same results in the region of Sétif (Algeria). The number of permanent workers on the farm does not exceed 2 AWU (Table 1).…”
Section: Resultssupporting
confidence: 65%
“…The average age of farmers is 35 years. Benidir et al (2017) reported the same results in the region of Sétif (Algeria). The number of permanent workers on the farm does not exceed 2 AWU (Table 1).…”
Section: Resultssupporting
confidence: 65%
“…The average calving interval in the region studied was longer than the 12-month interval reported by Benidir et al (2020) in eastern Algeria. Only 9 out of the surveyed farmers in the region used a calving pen, which is a pen designed to provide a comfortable and hygienic environment for cows giving birth.…”
Section: Discussioncontrasting
confidence: 55%
“…The level of education of breeders is often very low; 39.4% of breeders are unlettered, and 34.9% have a primary education level. Low literacy is a concept often observed in rural areas of Algeria, and it's partly explained by the farms location in remote areas without schools and cultural centers (Benidir et al, 2020;Mouhous et al, 2020).…”
Section: Socio-demographic Characteristicsmentioning
confidence: 99%